2010
DOI: 10.1111/j.1365-2362.2010.02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A serum levels in patients with aortic aneurysms of Marfan syndrome and atherosclerosis

Abstract: The significantly lower serum level of fetuin-A in the atherosclerotic aneurysm group supports the protective role of fetuin-A in the evolution of arterial calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…High plasma triglycerides and a low high density lipoprotein level are responsible for the development of diabetic nephropathy and cardiovascular diabetic complications [21] . Fetuin‐A inhibits vascular calcification and its serum level is low in patients with atherosclerosis [22] . It acts as a new cardiovascular risk factor and its level is associated with intima‐media thickness [23] .…”
Section: Clinical Context Of Fetuin‐amentioning
confidence: 99%
See 1 more Smart Citation
“…High plasma triglycerides and a low high density lipoprotein level are responsible for the development of diabetic nephropathy and cardiovascular diabetic complications [21] . Fetuin‐A inhibits vascular calcification and its serum level is low in patients with atherosclerosis [22] . It acts as a new cardiovascular risk factor and its level is associated with intima‐media thickness [23] .…”
Section: Clinical Context Of Fetuin‐amentioning
confidence: 99%
“…[21] Fetuin-A inhibits vascular calcification and its serum level is low in patients with atherosclerosis. [22] It acts as a new cardiovascular risk factor and its level is associated with intimamedia thickness. [23] The severity of atherosclerosis is inversely correlated with the fetuin-A level in serum.…”
Section: Structure Of Fetuin-amentioning
confidence: 99%
“…Low level is associated with increased intimal media thickness, apoptosis of vascular smooth muscle as well as vascular calcification which is associated with atherosclerosis. 15 This study revealed that the median serum level of Fetuin-A was significantly lower in psoriatic patients compared to control subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Risk factors for atherosclerosis, including obesity, smoking, hyperlipidemia, and hypertension do not differ from the general population [104]. In addition, carotid intimal thickness, a surrogate measure for coronary artery disease, has been shown not to differ between Marfan syndrome and the general population [105]. Together, this data suggests that patients with Marfan syndrome should carry the same risk of atherosclerotic coronary artery disease as those without.…”
Section: Atherosclerotic Coronary Artery Diseasementioning
confidence: 81%